Rigid Body Points Approximating Concentric Spheres in Alternating Sets of its Given Positions - Y. L. Sarkissyan (ՀՀ ԳԱԱ հրատ.)
The problem of determining the points of a body which in alternating sets of its given positions deviate least in the least square sense from concentric spheres is considered. Դիտարկվում է պինդ մարմնի այնպիսի կետերի որոշման խնդիրը, որոնք նրա նախանշված դիրքերի իրարահաջորդ բազմություններում ամենաքիչն են շեղվում համակենտրոն սֆերաներից` նվազագույն քառակուսիների իմաստով: Рассматривается задача определения точек твердого тела, которые в чередующихся множествах его положений наименее уклоняются от концентрических сфер в смысле наименьших квадратов.
Keywords: Physics; Mechanics; Science